PENGALAMAN MASYARAKAT DUSUN KALIBENING DALAM MELAKUKAN PERAWATAN HIPERTENSI DI MASA PANDEMI COVID-19 TAHUN 2021 - Katharina Olivia Titawardani; Antonius Yogi Pratama (Jurnal Ilmu Keperawatan Komunitas, 2021)
Background: Hypertension is a comorbid disease that can aggravate disease when infected with covid-19. Appropriate treatment can stabilize blood pressure. Patients with hypertension in Kalibening assume hypertension does not require special treatment. Patients with hypertension do not manage their diet, do physical activity without applying health protocols, and do not take hypertension medication. Method: The qualitative research with a phenomenological approach uses six participants with a purposive sampling technique. Data was collected using semi-structured interviews, observations on six respondents, and triangulation on two sources. It was analyzed by transcribing, coding, categorizing, and creating themes. Result: Themes found include blood pressure checks, stressors for people with hypertension during a covid-19 pandemic, hypertension control, adherence to types of drugs consumed, and family support. Participants are quite good at controlling hypertension and managing stress. They do not regularly control blood pressure, five are not good at managing their diet and do not regularly take their medication. Discussion: participants do not control blood pressure at health facilities for fear of contracting COVID-19, are able to manage stress, control hypertension by regulating diet, doing physical activity, sleeping 7-8 hours, not smoking and drinking alcohol. They do not take hypertension drugs for fear of complications. Families with hypertension are able to understand and pay attention to the health of their family members. Conclusion: Hypertension treatment during the covid-19 pandemic was carried out quite well in managing stress, controlling hypertension and family support. participants are not good at managing their diet and do not regularly take hypertension medication.